NFT Marketplaces as Catalysts of the Digital Creative Economy: Opportunities, Challenges, and Ethical Implications - Romano, Luca; Marchetti, Sofia (CV TOPAZART, 2024)
NFT marketplaces have revolutionized the digital creative economy by offering verifiable ownership, programmable royalties, and global reach for digital art and design. This paper analyzes how platforms like OpenSea, Rarible, Foundation, and LooksRare influence creative production, pricing dynamics, curation, and governance. Employing a mixed-methods approach—literate synthesis of recent literature, illustrative transaction dataset visualization, and praxis insight synthesis—we examine marketplaces across three dimensions: cultural/design practices, market structure, and ethical sustainability. The study highlights both liberatory affordances (access, upside for creators) and ethical frictions (volatility, discovery overload, royalty volatility, authenticity challenges, environmental concerns). We propose a “Responsible Marketplace Design” framework centered on transparency, creator equity, authenticity tooling, energy-conscious infrastructure, and fair curation. The paper concludes with actionable recommendations for creators, platforms, curators, and policy regulators, and outlines priority research directions including cross-chain interoperability, institutional valuation of on-chain works, and resilience of royalty systems.